2008
DOI: 10.1007/s12517-008-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Textural variations within different representative types of dune sediments in Kuwait

Abstract: Samples were collected from the surfaces of four types of typical dunes in order to identify variations in textural characteristics over their bodies. These dunes are barchan, climbing dune, falling dune, and nabkha. Statistical parameters vary from position to another and show that each dune has its own characteristics. It is well recognized that all the sediments of the studied dunes tend to be finer from borders toward the mid dune. Histograms and bivariate diagrams successfully differentiate between differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Such shrub from Leguminosae family that acts as organic fertilizer that enhances the quality of soil has led to the appearance of native plant species around area where A. spinosus cultivated such as, Fagonia indica, Fagonia The data obtained recently from governmental agencies during this study revealed that the mean cost of one cubic meter cleaned from the civilian and military infrastructures is equivalent to 5.33 USD, where nearly 3,160,661 m 3 of accumulated sand around infrastructures has been removed annually in Kuwait with a total cost of USD 4,169,766 [40]. The amount of encroached sand is doubled every 20 years according to [41]. The cost that each native plant can save was obtained by multiplying the average cost of one cubic meter removal of sand (5.33 USD) with the volume of sand around the native plant.…”
Section: Resultsmentioning
confidence: 83%
“…Such shrub from Leguminosae family that acts as organic fertilizer that enhances the quality of soil has led to the appearance of native plant species around area where A. spinosus cultivated such as, Fagonia indica, Fagonia The data obtained recently from governmental agencies during this study revealed that the mean cost of one cubic meter cleaned from the civilian and military infrastructures is equivalent to 5.33 USD, where nearly 3,160,661 m 3 of accumulated sand around infrastructures has been removed annually in Kuwait with a total cost of USD 4,169,766 [40]. The amount of encroached sand is doubled every 20 years according to [41]. The cost that each native plant can save was obtained by multiplying the average cost of one cubic meter removal of sand (5.33 USD) with the volume of sand around the native plant.…”
Section: Resultsmentioning
confidence: 83%
“…This wind speed is the minimum threshold for initiating sandstorms (Wilkerson 1991). Furthermore, RH during dust events ranges from 5 to 45% in the summer and winter, respectively (Al-Dousari et al 2008). While there is no specific research for this region that states at what particular visibility range dust substantially influences life patterns, the authors, who have local knowledge of the area, conclude that dust events that reduce visibility ranges to less than 4 km affect life patterns.…”
Section: Datamentioning
confidence: 98%
“…The Middle East region is surrounded by a desert ecosystem characterized by active aeolian conditions [3][4][5]. The SDS has a huge socioeconomic effect mainly on the marine environment [ 6,7], human health [ 8], aviation and oil industry [ 9,10]. The SDS passing over the region are considered to be major sources of sediments [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%